Pengaruh Pola Asuh Dialogis dan Metode Individualisasi pada Pendidikan Agama Islam Terhadap Sikap Anak Berdo'a Kepada Allah SWT di TK Birrul Waalidain Desa Takeran Kecamatan Takeran Kabupaten Magetan - Siti Muhayati (Jurnal Pendidikan, 2010)
The children’s attitude in praying against Allah is affected by the nurturing pattern of their parents and individualization method in kindergarten. If children are nurtured under dialogical pattern and individualized method in class, they will develop the positive attitude on praying against Allah. This research is attempted to identify the interrelationship among those variables above. Under a statistic analysis of t-test, the researcher finds that: 1) the dialogical nurturant pattern of parents has positive effect on the attitude on praying by Fo>Ft (38.55 > 4.11) under 0.05 of significant value. 2) the dialogical nurturant pattern and individualized method in class have significant effect on the attitude on praying by Fo>Ft ( 33.33>4.11) under 0.05 significant value. 3) the dialogical nurturant pattern and individualized method in class show interaction against the attitude on praying by Fp>Ft (6.32>4.11) under 0.05 significant value.